Respon Pertumbuhan dan Fisiologis Bayam (Amaranthus tricolor) yang Dipapar Timbal pada Sistem Hidroponik Sumbu - Yuspiah, Eka Fitriani; Rahayu, Yeni; Miftahuddin, Miftahuddin (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2021)
Green amaranth (Amaranthus tricolor) is a popular vegetable in Indonesia as a source of vitamins and minerals. This plant is susceptible to the contamination of heavy metals such as lead. This study aimed to analyze the growth responses and morphophysiological of A. tricolor in response to the application of lead in the forms of (Pb (NO3)2 using a wick hydroponic system. This study used factorial randomized design with four treatments of lead level, i.e. 0 ppm, 1 ppm, 3 ppm, and 5 ppm, repeated 2 times. Data were analyzed by analysis of one-way ANOVA and post hoc test by Duncan in P-value 5%. The growth responses were observed by measuring the plant height, the number of leaves, leaf color, shoot and roots fresh weight, also its dry weight. Whereas, the physiological responses were observed by analyzing the plant chlorophyll levels. The results obtained that the applications of (Pb(NO3)2 decreased plant height, leaf number, fresh weight of shoot and roots, dry weight of shoot and roots, also the chlorophyll levels. These lead treatments were affecting root loss, changed the color of leaves to become yellowish-green, and showing yellow-spotted close to the midrib. Analysis of lead uptake in stems and leaves showed that the absorption value increased along with the applications of (Pb(NO3)2 in the treatment. The treatment of 5 ppm of (Pb(NO3)2 showed the lowest result on all parameters.